2021
DOI: 10.1002/joc.7396
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal simulations of summer aerosol optical depth over the Arabian Peninsula using WRF‐Chem: Validation, climatology, and variability

Abstract: This study investigates the climatology and variability of summer aerosol optical depth (AOD) over the Arabian Peninsula (AP) using a long-term high-resolutionWeather Research and Forecasting model coupled with the chemistry module (WRF-Chem) simulation, available ground-based and satellite observations, and reanalysis products from 2008 to 2018. The simulated spatial distribution of the summer AOD agrees well with the satellite observations and reanalysis over the AP, with spatial correlation coefficients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…The mean seasonal spatial distributions of MODIS level‐2 DOD pixels over the three seasons displayed in Figure 2 indicate that the highest dust loadings are located over the southern parts of the AP and along the northeastern AP. The high dust loading in the southern parts of the AP is mainly due to dust emissions from the Rub’ Al Khali, as well as dust that is advected from the Iraq and Sudan regions (Karumuri et al., 2021; Kunchala et al., 2018). Among the three seasons in focus, strong dust loading is noticeable during the dust season of 2012, which is also captured by the WRF‐Chem simulations, as seen in the highest dust loadings over the AP in 2012 (Figures 2a and 2d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean seasonal spatial distributions of MODIS level‐2 DOD pixels over the three seasons displayed in Figure 2 indicate that the highest dust loadings are located over the southern parts of the AP and along the northeastern AP. The high dust loading in the southern parts of the AP is mainly due to dust emissions from the Rub’ Al Khali, as well as dust that is advected from the Iraq and Sudan regions (Karumuri et al., 2021; Kunchala et al., 2018). Among the three seasons in focus, strong dust loading is noticeable during the dust season of 2012, which is also captured by the WRF‐Chem simulations, as seen in the highest dust loadings over the AP in 2012 (Figures 2a and 2d).…”
Section: Resultsmentioning
confidence: 99%
“…WRF‐Chem has been widely used to investigate and predict aerosols, air quality, and dust storms, and accounts for the aerosol effect on radiation at regional scales (Grell et al., 2011; Karumuri et al, 2021; Karumuri, Ghude, et al., 2019; Marelle et al., 2017). For our experiments, WRF‐ChemV4.2.1 was configured with a single domain covering the AP region (20°−70°E and 0°−40°N) at 0.1° horizontal resolution and with 50 vertical levels up to model 10 hPa.…”
Section: Model and Data Setsmentioning
confidence: 99%
“…The spatial distribution of AOD and surface winds from WRF-Chem are compared against those of MODIS satellite and ERA-5 reanalysis, respectively (Figure 5). The AP is one of the world's largest dust source regions (Ginoux et al, 2001) and experiences the highest dust concentrations between March to September due to frequent passages of dust storms (e.g., Kunchala et al, 2018Kunchala et al, , 2019Dasari et al, 2019;Gandham et al, 2020Gandham et al, , 2022Karumuri et al, 2022). The spatial distribution of MODIS AOD exhibits high values over the southern Red Sea and central AP during PLD (Figure 5A), mainly associated with the presence of an anticyclonic circulation over the central AP.…”
Section: Wrf-chem Vs Satellite Measurementsmentioning
confidence: 98%
“…In general, it is difficult for WRF-Chem simulations to reproduce MODIS AOD. Balzarini et al (2015) found that WRF-Chem/MODIS AOD relationships can be a strong function of the chemical mechanism for both gas and aerosol phases, and Karumuri et al (2022) found that the relative bias between WRF-Chem and MODIS AOD can vary regionally within the simulation domain. However, some studies have had success reproducing MODIS AOD with WRF-Chem simulations (e.g., Chen et al, 2014;Siméon et al, 2021).…”
Section: Satellite-derived Aodmentioning
confidence: 99%